The History and Etymology of Cappadocian Fšáx 'Child', Pharasiot Fšáxi 'Boy'. (5th November 2020) - Janse, Mark; Vandewalle, Johan
Abstract: Cappadocian fšáx 'child' and Pharasiot fšáxi 'boy' are traditionally derived from Turkish uşak, assuming a hitherto unexplained fricativization of [u] to [f] and of word‐final [k] to [x] after the borrowing process. The latter cannot be attributed to Cappadocian or Pharasiot, however, as it is a common feature of Anatolian Turkish. In order to understand the former sound change, we have to assume an isolated case of high vowel fricativization in the articulated plural ta ušáxja > ta fšáxja → sg. to fšáx(i) by metanalysis, comparable to the generally acknowledged case of ta otjá > ta utjá > ta ftjá → sg. to ftí 'the ear'. We argue that fšáx(i) is an archaism in light of the parallel use of uşak → ušák reported in nineteenth‐century sources and the preservation of word‐final [x] even in dialects which seem to have borrowed words ending in [k] from Standard instead of Anatolian Turkish. The irregular inflection of Cappadocian fšáx suggests that it was borrowed as an adjective from Old Anatolian Turkish before it was substantivized in Ottoman Turkish, perhaps even from Old Turkish uvşak 'little': ta ufšáxa ta peðjá 'the little children' > ta fšáxa 'the little ones' by apheresis.